THE USE OF MINUTE MEETING ON THE SECOND PHASE OF CITY PARTNERSHIP (SISTER CITY) BETWEEN BANDA ACEH (THE REPUBLIC OF INDONESIA) AND HIGASHI-MATSUSHIMA (JAPAN) ON THE ACCELERATION OF RECONSTRUCTION - Abdul Halim; M. Putra Iqbal (Jurnal Ilmiah Mahasiswa Bidang Hukum Kenegaraan, 2020)
Abstract - This research aims to find out why the parties decided to use minute of meeting as their legal document instead of a MoU and to find out whether or not the 2nd phase of this sister city has followed the regulation. The research showed that the use Minute of Meeting in the Phase II as the basis for sister city between Banda Aceh and Higashimatsushima was due the MoU formed in the Phase I were satisfied the parties upon its implementation and wish to proceed to Phase II,both wanted to extend the collaboration and with a process that was not too long and it was found that the formation of a sister city legal document between Banda Aceh and Higashimatsushima not yet following the regulation of the Indonesian Republic's Foreign Minister Number: 09 / A / KP / XII / 2006/01 on the General Guidelines for Foreign Relations and Cooperation Procedures by Local government. It is suggested to the foreign ministry to shorten the process of forming sister city cooperation and for the local government should send initial information to the ministry related to the existence of a plan of cooperation with the government / foreign agency.Keywords : Banda Aceh, Higashimatsushima, Minute of Meeting, Sister City